Analisis Penggunaan Media Matching Gambar dan Mufrodat Bahasa Arab Perspektif Moh. Uzer Usman - Khairani, Riska; Loka, Fitrah; Mubarak, Muhammad Zaki (Prosiding Konferensi Nasional Bahasa Arab, 2023)
This research was conducted to analyze how teachers use picture matching and mufrodat gamemedia in the classroom based on Moh's perspective. Uzer Usman whose goal is to make studentsactive and enthusiastic in learning Arabic and the class atmosphere is no longer monotonous.This research was conducted with an interpretive paradigm, using a qualitative approach with acase study method. This research was carried out at Mtsn 4 Panyabungan. The data sources inthis research are 8th grade Arabic teachers, 8th grade students c. Data collection was carried outby observation, interviews and documentation. The population in this study was students ofclass 8 Mtsn 4 Panyabungan, the sample was class 8 C. The strategies used by researchers wereinterviews, observation and documentation. The results of this research show that the use ofimage matching game media and mufrodat based on Moh Uzer Usman's indicators has not beenfully implemented. 6 of the 9 indicators have been met, while the sections on reminding studentsof learning competencies and providing feedback have not been implemented by teachers.